2019
DOI: 10.3390/diseases7010018
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Gait in Parkinson’s Disease Using Wearable Motion Sensors: A Systematic Review

Abstract: : Parkinson’s disease (PD) is a progressive neurodegenerative disorder. Gait impairments are common among people with PD. Wearable sensor systems can be used for gait analysis by providing spatio-temporal parameters useful to investigate the progression of gait problems in Parkinson disease. However, various methods and tools with very high variability have been developed. The aim of this study is to review published articles of the last 10 years (from 2008 to 2018) concerning the application of wearable senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
91
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 45 publications
1
91
0
5
Order By: Relevance
“…PD is currently diagnosed based on motor impairments that are only present during progressive stages of the disease 41,42,43 . These clinical symptoms are caused by Lewy bodies aggregating in the brain and by degeneration of dopaminergic neurons in the substantia nigra.…”
Section: Discussionmentioning
confidence: 99%
“…PD is currently diagnosed based on motor impairments that are only present during progressive stages of the disease 41,42,43 . These clinical symptoms are caused by Lewy bodies aggregating in the brain and by degeneration of dopaminergic neurons in the substantia nigra.…”
Section: Discussionmentioning
confidence: 99%
“…Various types of sensory receptors, such as proprioceptors, give continuous feedback to the central nervous system. Various studies, with different methods, have been investigating the effects of peripheral bottom-up stimulation in order to reduce motor impairment in PD patients [13][14][15][16][17][18]. By enhancing the sensory feedbacks coming from the feet, bottom-up stimulation allows patients to better integrate peripheral inputs with motor control response during gait, producing a stimulating effect of central nervous system areas involved in human movement [18].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies, with different methods, have been investigating the effects of peripheral bottom-up stimulation in order to reduce motor impairment in PD patients [13][14][15][16][17][18]. By enhancing the sensory feedbacks coming from the feet, bottom-up stimulation allows patients to better integrate peripheral inputs with motor control response during gait, producing a stimulating effect of central nervous system areas involved in human movement [18]. Recent studies have shown the effectiveness of plantar mechanical stimulation in PD patients by applying punctual pressure in two specific areas of each foot (bottom-up rehabilitation) [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…smartphones, smart watches, smart clothing, etc. This, along with the fact that IMUs are now relatively inexpensive, has sparked their use for movement analysis in different disciplines, such as movement neuroscience (Shull et al, 2014;Picerno, 2017;O'Reilly et al, 2018), movement biomechanics and sports science (Salmond et al, 2017;Li et al, 2016;Johnston et al, 2019), and neurorehabilitation (Brognara et al, 2019;Dobkin, 2013;Hubble et al, 2015;Parker et al, 2020;Vienne et al, 2017;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%